2014
DOI: 10.1002/jsfa.6786
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on the fatty acid profiles of liver, subcutaneous fat and muscle from feedlot steers finished on diets supplemented with or without cinnamaldehyde or monensin

Abstract: The results indicate that the supplementation of CIN and MO to feedlot diet has limited effect on beef FA profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…There have also been reports of beneficial effects when cinnamaldehyde has been administered in the diet of meatproducing farm animals. He et al 94 found that supplementation with 800 mg of cinnamaldehyde/day to barley grain-silage finishing feed diet to feedlot steers had a limited effect on beef fatty acid profiles of liver, subcutaneous fat, and muscle. The authors suggest that dietary lipid levels might have been too low to affect the body fatty acid profile.…”
Section: ■ the Impact Of Cinnamaldehyde In Farm Animal Feedmentioning
confidence: 99%
“…There have also been reports of beneficial effects when cinnamaldehyde has been administered in the diet of meatproducing farm animals. He et al 94 found that supplementation with 800 mg of cinnamaldehyde/day to barley grain-silage finishing feed diet to feedlot steers had a limited effect on beef fatty acid profiles of liver, subcutaneous fat, and muscle. The authors suggest that dietary lipid levels might have been too low to affect the body fatty acid profile.…”
Section: ■ the Impact Of Cinnamaldehyde In Farm Animal Feedmentioning
confidence: 99%
“…The finding that DA modified fatty acid composition in the PCD muscle was unlike results reported for other essential oils that were administered to finishing cattle. He et al (2015) tested cinnamaldehyde in fattening feedlot steers and reported that it had no effect on the fatty acid profiles of the PCD. Rivaroli et al (2016) studied the impact of an essential oil blend that consisted, among other constituents, of oregano and garlic oil, on the fatty acid composition of feedlot bulls and concluded that the fatty acid composition was not affected.…”
Section: Discussionmentioning
confidence: 99%